The Higgs legacy of the LHC Run I - Corbett, Tyler; Éboli, Oscar J. P.; Gonçalves, Dorival; González Fraile, Juan; Plehn, Tilman; Rauch, Michael (Journal of high energy physics, 2015)
Based on Run I data we present a comprehensive analysis of Higgs couplings. For the first time this SFitter analysis includes independent tests of the Higgs-gluon and top Yukawa couplings, Higgs decays to invisible particles, and off-shell Higgs measurements. The observed Higgs boson is fully consistent with the Standard Model, both in terms of coupling modifications and effective field theory. Based only on Higgs total rates the results using both approaches are essentially equivalent, with the exception of strong correlations in the parameter space induced by effective operators. These correlations can be controlled through additional experimental input, namely kinematic distributions. Including kinematic distributions the typical Run I reach for weakly interacting new physics now reaches 300 to 500 GeV.
Gesehen am 08.12.2020